Membrane Type 1 Matrix Metalloprotease Cleaves Laminin-10 and Promotes Prostate Cancer Cell Migration - Elisabeth L. Bair; Man Ling Chen; Kathy McDaniel; Kiyotoshi Sekiguchi; Anne E. Cress; Raymond B. Nagle; George Timothy Bowden (Neoplasia: An International Journal for Oncology Research, 2005)
Disruption of the extracellular matrix by proteases is crucial for tumor invasion. Laminin-10 (Ln-10) has previously been identified as a substrate for cell migration and cell adhesion, and is present in the basal lamina (BL) of both normal prostate and prostate cancer. Here, we investigate a role for membrane type 1 matrix metalloprotease (MT1-MMP) in modifying this Ln-10-rich BL. MT1-MMP is a transmembrane member of the MMP family that has been demonstrated to be upregulated as prostate cancer progresses from normal to prostate intraepithelial neoplasia to invasive cancer, suggesting a role for MT1-MMP in the invasion of prostate cancer. We show that MT1-MMP cleaves the α5 chain of purified human Ln-10 from its 350-kDa form into 310-, 190-, 160-, and 45-kDa fragments. This cleavage causes a decrease in DU-145 prostate cancer cell adhesion to purified Ln-10, and an increase in transmigration of DU-145 cells through cleaved Ln-10. We also show that prostate cancer cells expressing membrane-bound MT1-MMP cleave the α5 chain of Ln-10. Ln α5-chain cleavage is also observed in human prostate cancer tissues. These findings suggest that prostate cancer cells expressing high levels of MT1-MMP have increased invasive potential through their ability to degrade and invade Ln-10 barriers.